99mTc-labelled multifunctional polyethylenimine-entrapped gold nanoparticles for dual mode SPECT and CT imaging. (31st October 2018) - Zhao, Lingzhou; Wen, Shihui; Zhu, Meilin; Li, Du; Xing, Yan; Shen, Mingwu; Shi, Xiangyang; Zhao, Jinhua
Abstract: In this study, we report the synthesis, characterization and utilization of 99m Tc-labelled polyethylenimine-entrapped gold nanoparticles ( 99m Tc-Au-PENPs) for dual mode single-photon emission computed tomography/computed tomography (SPECT/CT) imaging applications. Polyethylenimine (PEI) was selected as a platform to conjugate with diethylene triamine pentacetate acid (DTPA) and polyethylene glycol monomethyl ether to synthesize Au PENPs, followed by acetylation or hydroxylation modification of the remaining PEI surface amine groups and radiolabelling of 99m Tc. The generated multifunctional 99m Tc-Au-PENPs with different surface groups (acetyl or hydroxyl) were characterized via different methods. The Au PENPs before 99m Tc labelling are colloidally stable, haemocompatibility and noncytotoxic at an Au concentration up to 100 μM. The 99m Tc-labelled Au PENPs exhibit high radiochemical purity, good stability and SPECT/CT imaging performance of different organs and lymph node. The designed strategy to use the radionuclide labelling technique and PEI-facilitated versatile nanoplatform may be extended to develop various novel nanoprobes for precision imaging applications.